La corresponsabilidad familiar en el bienestar emocional de los usuarios del Centro Diurno de atención al Adulto Mayor del cantón Saraguro y la intervención del trabajador social. - Guamán Barrazueta, Yemeri Cristina (2025)
The present research aimed to analyze the influence of family co-responsibility on the emotional well-being of elderly users attending the Day Center in Saraguro, as well as the intervention of the social worker. To obtain information, a mixed methodology was applied, combining qualitative and quantitative techniques. This approach included interviews with the multidisciplinary team and the families of the users, as well as surveys administered to the users of the Day Center. Throughout the research, various barriers limiting family participation and emotional support for the elderly were identified, such as lack of time, distance, and lack of knowledge about elderly care. Additionally, the role of the social worker in facilitating this co- responsibility was analyzed, including intervention strategies that promote active family participation in the physical and emotional care of their elders. The research results reveal that effective family co-responsibility significantly contributes to the emotional well-being of the elderly, as those who receive consistent support from their families exhibit higher levels of satisfaction and a lower incidence of emotional problems. Conversely, the lack of family co- responsibility can exacerbate the emotional well-being of the elderly. As a result, this study proposes recommendations for improving family relationships and social intervention to optimize the care provided to the users attending the Day Center for the elderly in Saraguro.